Voluntary Debt Reduction : Incentives and Welfare. (IMF Working Papers; Working Paper ;, 1988)
This paper provides empirical evidence on the determinants of long-term growth performance in a sample of 55 developing countries grouped by income levels. The evidence indicates that a model incorporating the savings rate, export performance, expenditures on human capital development, the growth of population, and the real interest rate on external debt, explains the growth performance of these countries remarkably well. The model also suggests policies that would lead to higher long-run rates of growth.